Upaya Meningkatkan Prestasi Belajar Pendidikan Agama Hindu Melalui Penerapan Model Pembelajaran Cooperative Learning Tipe STAD Pada Siswa Kelas III Semester II SD Negeri 7 Bebandem Kabupaten Karangasem - Ida Bagus Wijana Putra (Jayapangus Press, 2021)
The purpose of this study was to determine the application of the STAD type of cooperative learning model to improve learning achievement of Hinduism students in the third semester of second semester of SD Negeri 7 Bebandem, Karangasem Regency in the 2015/2016 academic year. This research uses two rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is the third grade students of SD Negeri 7 Bebandem, Karangasem Regency. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. The results of the analysis showed that the application of the STAD Type Cooperative Learning learning model can improve student achievement and learning activity, marked by students' conceptual understanding with the percentage increase in the average grade value in the pre-cycle to cycle I and from cycle I to cycle II, respectively. .25% and 13.93%, from the average grade of 71.13 in the pre-cycle to 74.38 in the first cycle and 88.31 in the second cycle. The achievement of the percentage increase in absorption is the same as the percentage of the average grades from pre-cycle to cycle I and from cycle I to cycle II are 3.25% and 13.93%, namely from 71.13% in the pre-cycle to 74.38 % in the first cycle and 88.31% in the second cycle. While the classical learning mastery from pre-cycle to cycle I and from cycle I to cycle II respectively, namely learning completeness in pre-cycle is 37.5%, in cycle I 62.5% and in cycle II 100%. and the average cooperative skills of students are in the very skilled category. The conclusion of this study is that the application of the STAD type of cooperative learning learning model does have a positive impact on improving the learning achievement of Class III students at SD Negeri 7 Bebandem, Karangasem Regency, and this learning model can be used as an alternative to learning Hindu religious education.